1996
DOI: 10.1002/(sici)1097-0320(19960315)26:1<22::aid-cyto4>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Standardizing flow cytometry: construction of a standardized fluorescence calibration plot using matching spectral calibrators

Abstract: Calibration of flow cytometers is becoming an increasingly important issue for both quality control of instrument performance and quantitation of antibody binding capacity of cells. Due to the numerous different instruments and analysis software currently available, a standardized method of calibration is necessary if interlaboratory comparison of instrument performance and antibody binding is to be achieved. This report describes a new methodology to obtain a standard calibration plot that can be derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
127
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 132 publications
(127 citation statements)
references
References 12 publications
0
127
0
Order By: Relevance
“…We chose to employ absolute MESF units, which allowed numerical quantitation of the signal when compared with that of calibration beads, rather that to that of background. Such an approach for ZAP-70 analysis could offer a highly accurate and robust assay that could be standardized across multiple laboratories depending on uniformity of instrument settings and performing strictly defined fixing and staining protocols (19,20,28,29). Here, we present a novel quantitative flow cytometry analysis that enables electronic calculation of the average amount of ZAP-70 The analysis done according to the conventional method (11) shows that CLL patients with 20% ZAP-70 have a shorter time to progression than those with <20% positive patients (P ¼ 0.0026).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to employ absolute MESF units, which allowed numerical quantitation of the signal when compared with that of calibration beads, rather that to that of background. Such an approach for ZAP-70 analysis could offer a highly accurate and robust assay that could be standardized across multiple laboratories depending on uniformity of instrument settings and performing strictly defined fixing and staining protocols (19,20,28,29). Here, we present a novel quantitative flow cytometry analysis that enables electronic calculation of the average amount of ZAP-70 The analysis done according to the conventional method (11) shows that CLL patients with 20% ZAP-70 have a shorter time to progression than those with <20% positive patients (P ¼ 0.0026).…”
Section: Discussionmentioning
confidence: 99%
“…MESF is a relatively new type of analysis utilized in the field of flow cytometry to quantitate soluble cellular proteins (16)(17)(18). The MESF concept designates that a sample labeled with a fluorochrome has the same fluorescence intensity as an equivalent number of molecules of the fluorochrome free in a solution under the same environmental conditions (19,20). This fluorescence unit provides a tool to calculate the molecular equivalents of a particular protein within the cell and compare quantitative flow cytometry data over time, across instruments and laboratories (17,21).…”
mentioning
confidence: 99%
“…Mean fluorescence intensity of the cell population was converted to mean equivalent soluble fluorescein (MESF) using a standard curve generated with FITC-standard microspheres [19]. MESF was converted to equivalent mean number of Alexa488-PA molecules bound per cell as previously described [16] and plotted as a function of increasing Alexa488-PA concentration.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have been performed in an effort to better understand differences in reported data and in an attempt to better standardize flow cytometric measurements. A variety of sources of variation have been addressed and methods and reagents have been proposed to normalize many of these differences (4)(5)(6)8,9).…”
mentioning
confidence: 99%